Students’ Media Literacy Level at SMAN 1 Lore Selatan - Aprillianti Peluru (Sintuwu Maroso Journal of English Teaching, 2022)
Thisresearch aimed to describe students’ level of media literacy of SMAN 1 LoreSelatan. This type of research uses a quantitative survey method and the subjects of this research are 40 students of class XI SMAN 1 Lore Selatan. The data are collected by distributing questionnaire to students about the level of media literacy. The questionnaire used in this research is a questionnaire adopted from Kertanegara et al (2020) and Potter (2011) on media literacy. The results of this research indicate that the SMAN 1 Lore Selatan students have a medium level of media literacy, which means the students in this level can use the media to for their learning needs, understand information better, use certain strategies to meet their learning needs, and are more thorough in differentiating factual andhoax information.